Short-term scheduling model for a wind-hydro-thermal electricity system - Pereira, Sérgio (2012)
This study addresses the problem of the self-scheduling of an electricity system mainly based on hydro, fossil fuel thermal and wind power plants. A binary mixed integer non-linear optimization model is described and applied to short-term electricity planning of a system close to the expected Portuguese one on the year 2020. The model is written in a GAMS code and a global optimization solver is used to obtain the numerical results. The objective function encompasses the minimization of total system production costs through a centralized unit commitment. Different constraints, essentially related to operating parameters that characterize the power plants available for dispatch, are included in the model. The obtained results show the importance of the renewable energy sources seasonality on the thermal power plants operating conditions and on the total cost of the system.